The laws regulating the establishment and functions of the office of the pension funds adjudicator - Mashile, Khutso (My University, 2017)
This dissertation deals with the inception of the office of the Pension Fund Adjudicator in South Africa with comparison with the United Kingdom and Australia. The challenges faced by the office of the Pension Fund Adjudicator are one element that advised the composition of this dissertation. South Africa is a well developing country that carries well developed laws, including, the laws that deals with the pension fund complaints and this dissertation shall analyse and unpack those laws and principles that deals with the pension fund complaints.
Thesis (LLM.) -- University of Limpopo, 2017
Keywords: Pension funds; Pension fund laws; Pension trusts -- Law and legislation -- South Africa; Pensions -- Law and legislation -- South Africa; Retirement income -- Government policy -- South Africa; Social security -- Law and legislation -- South Africa